Addressing and Undoing Racism and Bias in the Medical School Learning and Work Environment. (December 2020) - Hess, Leona; Palermo, Ann-Gel; Muller, David
Abstract : Racism and bias are American medicine's fatal flaw. They permeate clinical practice and biomedical research, and their influence on medical education is even more profound because it is through medical education that racism and bias are perpetuated across generations and throughout history. This insidious influence has persisted despite the stated values of the medical profession and well-intentioned efforts to lessen their impact. The authors assert that racism and bias in the learning and work environment of medical school can be mitigated only through a formal change management process that leads to change that is institutionally transformational and individually transformative. The authors describe the sequence of events at one U.S. medical school, beginning in 2016, that led from student activism to an initiative that encompasses every functional sphere within medical education. They also reflect on personal and structural lessons learned during the course of designing and implementing this initiative. Eliminating racism and bias demands that medical educators embrace a change process that is lifelong, people-centered, incremental, and nonlinear. It requires the courage to constantly course correct while never losing sight of the ultimate goal: health care and medical education that are free of racism and bias.